Multifactorial heterogeneity of virus-specific T cells : Complex relationships during the progression of human chronic hepatitis B infection - Cheng, Yang (2018)
Human chronic viral infection is associated with T cell dysfunction and persistent yet highly variable viral burden. How such viral antigen-driven disease persistently reshapes the state of antigen-specific T cells by sustaining expression of inhibitory receptors remains unclear. By coupling mass cytometry and a highly multiplexed combinatorial pMHC tetramer staining strategy, we simultaneously probed 484 unique HLA-A*1101-restricted T cell epitopes spanning the entire hepatitis B virus (HBV) genome on CD8+ T cells from chronic hepatitis B patients across various clinical stages. We explored several novel epitope candidates and highlighted diverse cellular profiles on dominant epitopes. Together with the analysis of virus-specific TCR repertoires, various methods of high-dimensional phenotypic analysis of exhaustion and memory markers were explored in relation to HBV disease progression. We identified an immunodominant HBVcore169-specific CD8+ T cell population, and their memory and multi-functional profiles were linked to viral clearance. Additionally, T cells dysfunctionality was not linearly correlated with the reciprocal accumulation of multiple inhibitory receptors. This report works toward unraveling the unprecedented degree of antigen-specific T cell heterogeneity and T cell exhaustion during natural viral infection.